Personality and Teamwork on Employee Performance Through Organizational Commitment - Andi Salma Basallang; Maat Pono; Wahda Wahda (PINISI Discretion Review, 2023)
Employee performance in tertiary institutions has become the focus of research and attention in the field of human resource management. The challenges faced are maintaining and improving employee performance within the scope of the Faculty of Medicine to improve academic quality. What is the relationship between personality (PS) and teamwork (TW) on employee performance (EP) through organizational commitment (OC)? There are still few researchers who explore this question, especially within the scope of the Faculty of Medicine. The type of data to be used in this study is in the form of qualitative data and quantitative data. The population and sample in this study were Faculty of Medicine employees with status as PNS (Civil Servants) and Non PNS. The sampling method is census sampling. The analysis technique used is path analysis. The results of the study show that PS and TW variables have a significant effect on OC and EP. Results of this investigation also found that PS and TW have a significant effect on EP through OC. These findings contribute to an understanding of PS and effective TW, which can provide valuable insights for organizations to achieve high EP.